Pacemaker lead-induced progression of primary vs. secondary tricuspid regurgitation. (25th November 2020) - Riesenhuber, M; Spannbauer, A; Pezawas, T; Schukro, C; Gwechenberger, M; Stix, G; Anvari, A; Wrba, T; Khazen, C; Andreas, M; Laufer, G; Hengstenberg, C; et al.
Abstract: Background: Currently no data are available whether the implantation of right ventricular (RV) pacemaker (PM) lead worsens preexisting primary or secondary (functional due to RV dilatation, RVD) tricuspid regurgitation (TR). Purpose: The aim of the present retrospective analysis was to assess TR after PM implantation with a RV lead. Methods: Patients with PM implantation (n=990) were enrolled if they had routine echocardiography including assessment of TR before first implantation and immediately after. RVD and severity of TR were characterized visually. Based on RVD in baseline echocardiography, patients were divided into 2 groups: with primary TR (without preexisting RVD, n=743) or secondary TR (with preexisting RVD, n=243). Results: Lead-induced worsening of TR was present in both groups (Table 1). Progression from mild/moderate to severe TR was observed in 6.7% of patients with primary TR, compared to 25.6% of patients with secondary TR (P=0.001). Using an ordinal regression model, the probability to progress to severe TR with primary TR was 14.8% (95% CI 11.0%-19.7%), compared to 41.6% (95% CI 40.3%-42.8%) with secondary TR (P<0.001). Conclusion: Preexisting secondary TR was associated with higher rates of lead-induced progression to severe TR compared to primary TR. Leadless pacing or tricuspid valve clipping post-PM implantation could be an option for patients with preexisting secondary TR and indication for a PM. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): This study was supported by the European Union's Horizon 2020 Future and Emerging Technologies Programme [Grant number 732170].